Blow-molded product

A bimodal ethylene resin composition with controlled melt flow and density, enhanced by a metallocene catalyst system, addresses the balance of mechanical strength and processability in polyethylene blow-molding, resulting in a durable and resistant blow-molded article.

JP2025005466APending Publication Date: 2025-01-17TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023105602
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing polyethylene compositions, particularly ultra-high molecular weight polyethylene, face challenges in achieving a balance between mechanical strength, processability, and versatility in molding processes, especially blow-molding, with existing modifications not fully addressing these needs.

Method used

A blow-molded article composed of a specific ethylene resin with bimodal molecular weight distribution and polyethylene, characterized by controlled melt flow rates and density, utilizing a catalyst system with metallocene complexes to enhance mechanical properties and environmental load resistance.

Benefits of technology

The solution results in a blow-molded article with excellent impact resistance, environmental load resistance, and a thinner, longer-lasting design suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005466000001
    Figure 2025005466000001
  • Figure 2025005466000002
    Figure 2025005466000002
Patent Text Reader

Abstract

To provide a blow-molded product made from a polyethylene composition comprising polyethylene and a high molecular weight ethylene resin with a bimodal molecular weight, demonstrating superior Charpy impact strength and resistance to environmental stress.SOLUTION: The present invention provides a blow-molded product made from a polyethylene composition, comprising: an ethylene resin (a) with an HLMFR of 0.01-100 g / 10 min at 190°C under 21.6 kg load, and a bimodal elution curve measured by GPC; and polyethylene (b) with an MFR of 0.01-10 g / 10 min at 190°C under 2.16 kg load, and a density of 925-980 kg / m3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a specific blow molded article, and more specifically to a blow molded article which is excellent in impact resistance and environmental load resistance, and which is expected to have a thinner wall and a longer life as a molded article. [Background technology]

[0002] Polyethylene is a resin used in a wide range of applications, and in order to make it suitable for each application, technologies have been proposed to control the molecular weight distribution and composition by combining two or more resin components, thereby improving various physical properties and appearance. For example, an increase in higher molecular weight components improves mechanical strength but decreases moldability, while an increase in lower molecular weight components decreases mechanical strength but improves moldability.

[0003] As a method for combining two or more types of polyethylene components, there have been proposed a method in which each component is polymerized and then blended by melt kneading or dry blending, a method in which multi-stage polymerization is carried out continuously, a method in which two or more types of polyethylene components are simultaneously produced by adding a plurality of transition metal catalysts to a polymerization system, a method in which a combination of these is carried out, etc. In addition, a resin modifier has also been proposed (see, for example, Patent Document 1) that is blended with a target material to modify the physical properties, appearance, etc. of the target material.

[0004] In the manufacture of polyethylene molded articles by stretching, spinning, blow molding, injection molding, inflation molding, and extrusion molding, materials with good moldability and physical properties are generally required. In recent years, there has been a demand for lighter weight and thinner walls to reduce costs, while excellent mechanical strength is also required.

[0005] Ultra-high molecular weight polyethylene, which has attracted attention in recent years (see, for example, Patent Documents 2 and 3), has an extremely high molecular weight equivalent to a viscosity average molecular weight (hereinafter sometimes referred to as Mv) of 1 million or more, and therefore has excellent impact resistance, self-lubrication, abrasion resistance, weather resistance, chemical resistance, dimensional stability, etc., and has high physical properties comparable to those of engineering plastics. For this reason, attempts have been made to apply it to uses such as sheets, films, high-strength fibers, sliding members, lining materials, line parts in the food industry, machine parts, artificial joints, sporting goods, microporous membranes, and separators by various molding methods.

[0006] However, because of its high molecular weight, ultra-high molecular weight polyethylene has extremely low fluidity when melted, and it is difficult to melt mold it like ordinary polyethylene, which has a molecular weight ranging from several tens of thousands to about 300,000.Therefore, ultra-high molecular weight polyethylene is molded by a method such as direct sintering of the polymer powder obtained by polymerization, compression molding, molding using a ram extruder in which extrusion molding is performed while intermittently compressing, or a method in which ultra-high molecular weight polyethylene is extruded into a sheet, film, or fiber shape in a state where it is uniformly mixed with a plasticizer, and then stretched as the case may be, and then the solvent is removed.

[0007] In order to improve the moldability of ultra-high molecular weight polyethylene and its mixability with other resins, a method of adding low molecular weight polyethylene has been proposed (see, for example, Patent Documents 4 and 5), and an ultra-high molecular weight polyethylene exhibiting a specific melting behavior has been proposed (see, for example, Patent Document 6). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-179304 A [Patent Document 2] Patent No. 4868853 [Patent Document 3] Patent No. 6405888 [Patent Document 4] Patent No. 4173444 [Patent Document 5] Patent No. 7071966 [Patent Document 6] JP 2021-172716 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, although the modified material proposed in Patent Document 1 was effective in improving processability to a certain extent, further improvement was required in terms of improving mechanical strength.

[0010] Moreover, Patent Documents 2 and 3 merely propose ultra-high molecular weight polyethylene, and have problems with moldability. The proposals in Patent Documents 4 to 6 also only improve the processability of ultra-high molecular weight polyethylene, and still have problems with versatility.

[0011] Therefore, there has been a demand for the development of blow molded articles that have excellent mechanical properties without impairing the processability, particularly blow moldability, of general-purpose resins. [Means for solving the problem]

[0012] Means for Solving the Problems The present inventors conducted intensive studies to solve the above problems and found that a blow molded article made from a composition of an ethylene-based resin and polyethylene having specific melting properties and molecular weight configuration can be a blow molded article having excellent properties such as excellent Charpy impact strength and environmental load resistance, as well as excellent product appearance, and thus completed the present invention.

[0013] That is, the present invention relates to a blow-molded article characterized by being made of a polyethylene composition containing an ethylene-based resin (III) satisfying the following characteristics (III-a) and (III-b) and a polyethylene (IV) satisfying the following characteristics (IV-a) and (IV-b): Characteristics (Ha): Compliant with JIS 6922-2:1997, melt flow rate (hereinafter sometimes referred to as HLMFR) at a temperature of 190°C and a load of 21.6 kg is 0.01 to 100 g / 10 min. Characteristics (cb): The elution curve measured by gel permeation chromatography (hereinafter sometimes referred to as GPC) is bimodal. Characteristics (ii a): Melt flow rate (hereinafter sometimes referred to as MFR) of 0.01 to 10 g / 10 min at a temperature of 190°C and a load of 2.16 kg according to JIS 6922-2:1997. Property (ii) b: Density measured according to JIS K6922-1 (1997) is 925-980 kg / m 3 .

[0014] The present invention will be described in detail below.

[0015] The blow molded article of the present invention is composed of an ethylene-based resin (c) having an HLMFR of 0.01 to 100 g / 10 min and a bimodal elution curve measured by GPC, and an ethylene-based resin (d) having an MFR of 0.01 to 10 g / 10 min and a density of 925 to 980 kg / m 3 The polyethylene composition comprises at least the polyethylene (iv).

[0016] The ethylene resin (iii) is a bimodal ethylene resin with a relatively high molecular weight that exhibits melting behavior and a bimodal elution curve measured by GPC that exhibits two peaks, and examples thereof include ethylene homopolymers and ethylene-α-olefin copolymers, with the α-olefins being, for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and ethylene homopolymers are preferred because they provide blow molded articles with excellent impact strength and environmental load resistance. Similarly, the polyethylene (iv) can be, for example, ethylene homopolymers and ethylene-α-olefin copolymers, with the α-olefins being, for example, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, etc., and ethylene homopolymers are preferred because they provide blow molded articles with excellent impact strength and environmental load resistance.

[0017] The ethylene-based resin (c) has (ca) an HLMFR of 0.01 to 100 g / 10 min and exhibits melt fluidity. If it is less than 0.01 g / 10 min, the melt fluidity is poor and the processability when forming a blow molded article is poor. On the other hand, if it is more than 100 g / 10 min, the blow molded article will have poor mechanical properties.

[0018] The ethylene-based resin (C) constituting the blow molded article of the present invention is an ethylene-based polymer having a bimodal molecular weight distribution, and can be used to give a blow molded article having an excellent balance between processability and environmental load resistance. Therefore, it is preferable that the ethylene-based resin (C) has a unimodal crystal melting peak (hereinafter sometimes referred to as Tm1) in the 1st scan measured using a differential scanning calorimeter (hereinafter sometimes referred to as DSC) (Cc) by heating from 0°C to 230°C at a heating rate of 10°C / min (hereinafter sometimes referred to as 1st scan).

[0019] Moreover, since the ethylene-based resin (c) gives a blow molded article having an especially excellent balance between dispersibility with the polyethylene (d) and improved mechanical properties, (c-d) the molecular weight distribution (hereinafter sometimes referred to as Mw / Mn) expressed as the weight average molecular weight (hereinafter sometimes referred to as Mw) / number average molecular weight (hereinafter sometimes referred to as Mn) calculated as linear polyethylene as measured by GPC is preferably 4.0 or more and less than 50, and more preferably 4.0 or more and 30 or less. Furthermore, since the blow molded article has excellent yellowing resistance and weather resistance, (c-e) the ash content preferably contains less than 2 ppm of titanium and less than 50 ppm of chlorine.

[0020] The ethylene resin (III) constituting the blow molded article of the present invention is an ethylene polymer having a bimodal molecular weight distribution, and preferably contains a specific ultra-high molecular weight polyethylene component (III) as a specific component, since it results in a blow molded article having an excellent balance between processability and weather resistance. In this case, the bimodal molecular weight distribution is preferably one that has a bimodal elution curve measured by GPC, is expressed as a differential molecular weight distribution (x-axis: Log[M], y-axis: differential distribution value), and satisfies (III-f-1) to (III-f-3) when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log[M], y-axis: differential distribution value) and is peak-divided into two normal distributions (normal distribution of ultra-high molecular weight polyethylene component (III) and normal distribution of polyethylene component (III)) according to the following formula (i). f(x)=a×(1 / (2π(σ 2 )) (1 / 2) ) exp(-((x-μ) 2 ) / (2(σ 2 ))) Formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the mean.) (c-f-1) The ultra-high molecular weight polyethylene component (a) (hereinafter may be referred to as component (a)) represented as the high molecular weight peak component has an Mw of 900,000 to 5,000,000, with an Mw / Mn of 2.0 to 5.0, (c-f-2) The polyethylene component (b) (hereinafter may be referred to as component (b)) represented as the low molecular weight peak component has an Mw of 10,000 to 500,000, with an Mw / Mn of 2.0 to 5.0, and (c-f-3) the component (a) / component (b) (weight ratio) is greater than 5 / 95 and less than 80 / 20, and it is particularly preferred that the component (a) / component (b) (weight ratio) is 10 / 90 to 50 / 50.

[0021] When the ethylene-based resin (iii) is one in which the ultra-high molecular weight component (i) and the low molecular weight component (ii) coexist in a specific ratio, when it is blended with polyethylene (iv), the component (i) can be highly dispersed, making it possible to highly modify the tensile properties of the blow-molded article without impairing the appearance.

[0022] The ethylene-based resin (iii) constituting the blow molded article of the present invention may be any resin as long as it satisfies the above-mentioned characteristics. In particular, it is preferable that the resin is produced using a metallocene catalyst, since it is easy to control the molecular weight and molecular weight distribution and to produce an (ultra)high molecular weight resin. In particular, examples of a method for producing the ethylene-based resin (iii) having both components (i) and (ii) include a method using a co-supported catalyst in which two or more types of metallocene complexes are supported on a carrier as the catalyst system, and a method using a multi-stage polymerization of two or more stages.

[0023] The polymerization method of the ethylene-based resin (iii) may be, for example, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, a slurry polymerization method, etc., among which, the slurry polymerization method is preferable since it enables the production of an ethylene-based resin with a regular particle shape. The solvent used in the slurry polymerization method may be any organic solvent that is generally used, for example, benzene, toluene, xylene, pentane, hexane, heptane, etc., and liquefied gases such as isobutane and propane, and olefins such as 1-butene and 1-hexene can also be used as the solvent.

[0024] The production catalyst used to produce the ethylene-based resin (iii) may be any catalyst capable of producing the ethylene-based resin. For example, in the case of multi-stage polymerization, a metallocene catalyst obtained from at least a transition metal compound (A-1), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used. For example, in the case of a co-supported catalyst method, a metallocene catalyst obtained from at least a transition metal compound (A-1), a transition metal compound (A-2), an organically modified clay modified with an aliphatic salt (B), and an organoaluminum compound (C) may be used.

[0025] Examples of the transition metal compound (A-1) include a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, and a transition metal compound having a (substituted) indenyl group and a (substituted) fluorenyl group. In this case, examples of the transition metal include zirconium and hafnium. Among these, a zirconium compound having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group and a hafnium compound having a (substituted) cyclopentadienyl group and an amino group-substituted fluorenyl group are preferred, as they enable efficient production of an ethylene-based resin suitable for forming a blow-molded article.

[0026] More specifically, for example, diphenylmethylene(1-indenyl)(9-fluorenyl)zirconium dichloride, diphenylmethylene(1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(4-phenyl-1-indenyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride, )(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bis (dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dimethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-ethyl-9-fluorenyl)zirconium dichloride,Diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-ethyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diethylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-n-propyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl)(2-(diphenylmethylene)(cyclopentadienyl) diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-isopropyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-7-n-butyl-9-fluorenyl)zirconium dichloride Examples of zirconium compounds include diphenylmethylene(cyclopentadienyl)(2-(diisopropylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride and diphenylmethylene(cyclopentadienyl)(2-(dibenzylamino)-7-t-butyl-9-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0027] Examples of the transition metal compound (A-2) include a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) fluorenyl group, a transition metal compound having a (substituted) cyclopentadienyl group and a (substituted) indenyl group, and a transition metal compound having a (substituted) indenyl group and a (substituted) indenyl group.

[0028] More specifically, dimethylsilanediylbis(cyclopentadienyl)zirconium dichloride, diethylsilanediylbis(cyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(cyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(cyclopentadienyl)zirconium dichloride, Silanediylbis(methylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(methylcyclopentadienyl)zirconium dichloride, dimethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diethylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, dicyclohexylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride, diphenylsilanediylbis(2,4-dimethylcyclopentadienyl)zirconium dichloride silanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(indenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride silanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(4,7-dimethylindenyl)]zirconium dichloride, dimethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diethylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, dicyclohexylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, diphenylsilanediyl[(cyclopentadienyl)(2,4,7-trimethylindenyl)]zirconium dichloride, bis(indenyl)zirconium dichloride, isopropylidenebis(indenyl)zirconium dichloride, (methyl)(phenyl)methylenebis(indenyl)zirconium dichloride, diphenyl Phenylmethylene bis(indenyl)zirconium dichloride, ethylene bis(indenyl)zirconium dichloride, isopropylidene bis(2-methylindenyl)zirconium dichloride, (methyl)(phenyl)methylene bis(2-methylindenyl)zirconium dichloride, diphenylmethylene bis(2-methylindenyl)zirconium dichloride, ethylene bis(2-methylindenyl)zirconium dichloride, isopropylidene bis(tetrahydroindenyl)zirconium dichloride , (methyl)(phenyl)methylenebis(tetrahydroindenyl)zirconium dichloride, diphenylmethylenebis(tetrahydroindenyl)zirconium dichloride, ethylenebis(tetrahydroindenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride dichloride, ethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, (methyl)(phenyl)methylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride, ethylene(cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride; zirconium compounds in which the dichloro form of these compounds is replaced with a dimethyl form, a diethyl form, a dihydro form, a diphenyl form, or a dibenzyl form; and hafnium compounds in which the zirconium of these compounds is replaced with hafnium.

[0029] Examples of the organically modified clay (B) modified with an aliphatic salt include N,N-dimethyl-behenylamine hydrochloride, N-methyl-N-ethyl-behenylamine hydrochloride, N-methyl-Nn-propyl-behenylamine hydrochloride, N,N-dioleyl-methylamine hydrochloride, N,N-dimethyl-behenylamine hydrofluoride, N-methyl-N-ethyl-behenylamine hydrofluoride, N-methyl-Nn-propyl-behenylamine hydrofluoride, N,N-dioleyl-methylamine hydrofluoride, N,N-dimethyl-behenyl ... behenylamine hydrobromide, N-methyl-N-ethyl-behenylamine hydrobromide, N-methyl-Nn-propyl-behenylamine hydrobromide, N,N-dioleyl-methylamine hydrobromide, N,N-dimethyl-behenylamine hydroiodide, N-methyl-N-ethyl-behenylamine hydroiodide, N-methyl-Nn-propyl-behenylamine hydroiodide, N,N-dioleyl-methylamine hydroiodide, N,N-dimethyl-behenylamine sulfate, N-methyl-N-ethyl-behenylamine sulfate aliphatic amine salts such as N-methyl-Nn-propyl-behenylamine sulfate and N,N-dioleyl-methylamine sulfate; P,P-dimethyl-behenylphosphine hydrochloride, P,P-diethyl-behenylphosphine hydrochloride, P,P-dipropyl-behenylphosphine hydrochloride, P,P-dimethyl-behenylphosphine hydrofluoride, P,P-diethyl-behenylphosphine hydrofluoride, P,P-dipropyl-behenylphosphine hydrofluoride, P,P-dimethyl-behenylphosphine hydrobromide, P,P- Examples of the clay modified with an aliphatic salt include aliphatic phosphonium salts such as diethyl-behenylphosphine hydrobromide, P,P-dipropyl-behenylphosphine hydrobromide, P,P-dimethyl-behenylphosphine hydroiodide, P,P-diethyl-behenylphosphine hydroiodide, P,P-dipropyl-behenylphosphine hydroiodide, P,P-dimethyl-behenylphosphine sulfate, P,P-diethyl-behenylphosphine sulfate, and P,P-dipropyl-behenylphosphine sulfate.

[0030] The clay compound constituting the organically modified clay (B) may be any compound as long as it belongs to the category of clay compounds. In general, the organically modified clay (B) is formed by stacking many layers called silicate layers, which are composed of a tetrahedral sheet of silica tetrahedrons connected in two dimensions and an octahedral sheet of alumina octahedrons or magnesia octahedrons connected in two dimensions in a 1:1 or 2:1 ratio. The Si in some of the silica tetrahedra is replaced by Al, the Al in the alumina octahedrons by Mg, and the Mg in the magnesia octahedrons by Li, etc., resulting in a lack of positive charges within the layers and the layers as a whole being negatively charged. In order to compensate for this negative charge, Na is introduced between the layers. + Or Ca 2+ As the clay compound, there are natural or synthetic products such as kaolinite, talc, smectite, vermiculite, mica, brittle mica, and malachite, and these can be used, among which smectite is preferred because of its ease of availability and ease of organic modification, and among smectites, hectorite or montmorillonite is even more preferred.

[0031] The organically modified clay (B) can be obtained by introducing the aliphatic salt between the layers of the clay compound to form an ion complex. When preparing the organically modified clay (B), it is preferable to select conditions of a clay compound concentration of 0.1 to 30% by weight and a treatment temperature of 0 to 150°C. The aliphatic salt may be prepared as a solid and dissolved in a solvent for use, or a solution of the aliphatic salt may be prepared by chemical reaction in a solvent and used as is. As for the reaction ratio of the clay compound and the aliphatic salt, it is preferable to use an equivalent or greater amount of aliphatic salt relative to the exchangeable cations of the clay compound. Examples of the treatment solvent that can be used include aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene and toluene; alcohols such as ethyl alcohol and methyl alcohol; ethers such as ethyl ether and n-butyl ether; halogenated hydrocarbons such as methylene chloride and chloroform; acetone; 1,4-dioxane; tetrahydrofuran; water, and the like. It is preferable to use alcohols or water alone or as one component of the solvent.

[0032] In addition, the particle size of the organically modified clay (B) constituting the production catalyst is not limited, and is preferably 1 to 100 μm, since it is excellent in efficiency during catalyst preparation and efficiency during ethylene-based resin production. There is also no limit to the method of adjusting the particle size, and large particles may be crushed to an appropriate particle size, small particles may be granulated to an appropriate particle size, or crushing and granulation may be combined. In addition, the particle size may be adjusted either on the clay before organic modification or on the organically modified clay after modification.

[0033] As the organoaluminum compound (C), any compound that belongs to the category called an organoaluminum compound can be used, and examples thereof include alkylaluminum such as trimethylaluminum, triethylaluminum, and triisobutylaluminum.

[0034] The proportions of the transition metal compounds (A-1) and (A-2) (hereinafter, the transition metal compounds (A-1) and (A-2) may be collectively referred to as component (A)), the organic modified clay (B) (hereinafter, also referred to as component (B)), and the organoaluminum compound (C) (hereinafter, also referred to as component (C)) that constitute the production catalyst are not subject to any restrictions so long as they can be used as a catalyst for producing polyethylene. In particular, in order to provide a production catalyst that can efficiently produce the ethylene-based resin (C), the molar ratio per metal atom of component (A) to component (C) is preferably in the range of component (A):component (C)=100:1 to 1:100,000, and more preferably in the range of 1:1 to 1:10,000. Furthermore, the weight ratio of component (A) to component (B) is preferably component (A):component (B)=10:1 to 1:10000, and more preferably in the range of 3:1 to 1:1000.

[0035] Regarding the preparation method of the production catalyst, any method may be used as long as it is possible to prepare a production catalyst containing the (A) component, the (B) component, and the (C) component, and for example, a method of mixing the (A), (B), and (C) components in a solvent inert to the respective components, or using the monomer to be polymerized as a solvent, can be mentioned. In addition, there is no restriction on the order in which these components are reacted, and there is no restriction on the temperature and time of this treatment. In addition, it is also possible to prepare a production catalyst using two or more kinds of each of the (A), (B), and (C) components.

[0036] The polymerization conditions such as polymerization temperature, polymerization time, polymerization pressure, and monomer concentration when producing the ethylene resin (iii) can be arbitrarily selected, and among them, it is preferable to carry out the polymerization at a polymerization temperature of 0 to 100°C, for a polymerization time of 10 seconds to 20 hours, and at a polymerization pressure of normal pressure to 100 MPa. It is also possible to adjust the molecular weight by using hydrogen or the like during the polymerization. The polymerization can be carried out by any method such as a batch method, a semi-continuous method, or a continuous method, and it is also possible to carry out the polymerization in two or more stages by changing the polymerization conditions. The polymer particles obtained after the polymerization is completed can be separated and recovered from the polymerization solvent by a conventionally known method, and dried to obtain the product.

[0037] The polyethylene (iv) constituting the blow molded article of the present invention has an MFR of 0.01 to 10 g / 10 min and a density of 925 to 980 kg / m 3 Examples of the polyethylene include those mentioned above, and among them, high density polyethylene is preferable, and examples of such polyethylene include (product name) Nipolon Hard (manufactured by Tosoh Corporation) and (product name) Hi-Zex (manufactured by Prime Polymer Co., Ltd.). Here, the polyethylene having an MFR of less than 0.01 g / 10 min or a density of 980 kg / m 3 If it exceeds this limit, the product will have poor processability, be prone to melt fracture, and have a poor appearance. On the other hand, if the MFR exceeds 10g / 10min or the density exceeds 925kg / m 3 If it is less than this, the mechanical strength will be poor.

[0038] The blow molded article of the present invention is made of a polyethylene composition containing at least the above-mentioned ethylene-based resin (c) and polyethylene (d). The amount of the polyethylene composition may be any as long as the blow molded article exhibits excellent mechanical strength. In particular, since the balance between the mechanical properties and processability is excellent, the polyethylene composition preferably contains 1 to 100 parts by weight of the ethylene-based resin (c), and more preferably 5 to 50 parts by weight, per 100 parts by weight of the polyethylene (d).

[0039] The polyethylene composition constituting the blow molded article of the present invention may be prepared by any method, and examples thereof include a method of blending and kneading, by a kneading machine or the like, 1 to 100 parts by weight of an ethylene-based resin (iii) per 100 parts by weight of polyethylene (iv), and further, as necessary, additives usually used in polyolefins, such as weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, lubricants, pigments, nucleating agents, plasticizers, antioxidants, antioxidants, UV absorbers, neutralizing agents, surfactants, slip agents, and inorganic or organic fillers. The conditions for such blending may be any as long as a polyethylene composition can be obtained, and examples thereof include a method of melt blending pellets of the ethylene-based resin (iii) and pellets of the polyethylene (iv) by an extruder or the like.

[0040] The blow molded article of the present invention can be obtained by molding the polyethylene composition by a method known as blow molding. The blow molding in this case is a method in which a resin charged from a hopper is melt-kneaded in an extruder, a cylindrical parison is extruded, sandwiched between a predetermined die, and molded into a container using air or the like. For example, blow molding in which the polyethylene composition is prepared as described above, the polyethylene composition is melted in the extruder part of a blow molding machine, the extruded molten material such as a parison is sandwiched between a die, and then a gas or the like is blown into the molten material to form a shape, or injection blow molding in which a molten material is injected and a gas or the like is blown into the molten material at the same time to form a shape, may be used. Alternatively, a method in which polyethylene (d), ethylene-based resin (c), and other compounds are blended and charged directly into a hopper to form a blow molded article may be used, or a method in which the mixture is kneaded in advance using a single-screw extruder or the like and then blow molded.

[0041] The temperature inside the extruder when producing the blow molded article of the present invention may be any temperature that allows molding, and a temperature of 170 to 240°C is preferred because it enables efficient melt-kneading and reduces the possibility of a decrease in strength or deterioration of appearance due to resin deterioration.

[0042] The screw shape of the extruder portion in this case may be any shape capable of sufficiently melt-kneading the polyethylene resin, and the length of the feed section relative to the effective screw length is preferably 0.35 to 0.50 since this allows the polyethylene composition to be sufficiently preheated. Also, the length of the compression section relative to the effective screw length is preferably 0.30 to 0.40 since this allows sufficient melt-kneading. Furthermore, the ratio (L / D) of the effective screw length (L) to the screw diameter (D) is preferably 24 to 32 since this allows sufficient melt-kneading with a low motor load.

[0043] When producing the blow molded article of the present invention, it is preferable that the ratio of the length of the metering section to the effective screw length is 0.20 to 0.30, since this enables extrusion with little fluctuation in the extrusion rate (surging phenomenon).

[0044] The blow molded article of the present invention has excellent mechanical strength, and therefore can be made thinner and lighter. 2 It is preferable that the above is the case.

[0045] The blow molded article of the present invention has excellent mechanical strength and is expected to enable the molded article to be made thinner and have a longer life, and can be used as a plastic tank, a plastic drum, a crash-resistant drum, a liquid medicine container, particularly a large liquid medicine container, a food container, a cosmetic bottle, a fuel tank, a pipe, a plastic bag, etc. Effect of the Invention

[0046] The blow molded article of the present invention is excellent in impact resistance and environmental load resistance, and therefore, the molded article can be made thinner, have a longer life, and is lighter in weight. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.

[0048] Unless otherwise specified, the reagents used were either commercially available or synthesized according to known methods.

[0049] The organically modified clay was pulverized using a jet mill (product name: CO-JET SYSTEM α MARK III, manufactured by Seishin Enterprise Co., Ltd.), and the particle size after pulverization was measured using a Microtrack particle size distribution measuring device (product name: MT3000, manufactured by Nikkiso Co., Ltd.) using ethanol as a dispersant.

[0050] The preparation of the catalyst for production, the production of the ethylene resin, and the purification of the solvent were all carried out under an inert gas atmosphere. The hexane solution (20 wt%) of triisobutylaluminum manufactured by Toso Finechem Co., Ltd. was used.

[0051] Furthermore, various physical properties of the ethylene resin and polyethylene were measured by the methods shown below.

[0052] ~Measurement of Mw and Mn~ Measurements were performed using an ultra-high temperature GPC (Senshu Scientific, product name SSC-7110) equipped with a column (Tosoh, product name TSKgel GMHHR-H(S)HT) with 1-chloronaphthalene as the eluent at a column temperature of 210°C, a sample concentration of 0.5mg / ml, and an injection volume of 0.2ml. The molecular weight calibration curve was calibrated using a standard polystyrene sample, and Mw and Mn were converted to linear polyethylene.

[0053] ~MFR~ The melt flow rate was measured at a temperature of 190° C. under a load of 2.16 kg in accordance with JIS6922-2:1997.

[0054] ~HLMFR~ The melt flow rate was measured at a temperature of 190° C. and a load of 21.6 kg in accordance with JIS6922-2:1997.

[0055] ~Measurement of thermal melting of ethylene resin~ Using a DSC (product name: DSC6220, manufactured by SII NanoTechnology, Inc.), the temperature was raised from 0°C to 230°C at a heating rate of 10°C / min (1st scan), and the crystal melting peak (Tm) and heat of fusion (ΔH) of the 1st scan were measured.

[0056] ~Titanium content~ 10 mg of ethylene resin was burned in oxygen, the ash obtained was dissolved in alkali, and the titanium contained in the test liquid was quantified using ICP-AES (PerkinElmer, (product name) Optima 8300).

[0057] ~Chlorine content~ 10 mg of ethylene resin was burned in oxygen, and the resulting ash was mixed with pure water to make the total volume 50 ml to prepare a test liquid. The chloride ions contained in the test liquid were quantified using ion chromatography (manufactured by Tosoh Corporation, product name: IC-2010).

[0058] ~Charpy impact strength~ The impact strength was measured using a universal impact tester (ISO-PE-Z43, manufactured by Toyo Seiki Seisakusho) with a support distance of 62 mm and a pendulum load of 4 J. Test specimens were cut out from the blow molded bodies, and rectangular test specimens measuring 80 mm x 10 mm x 2.0 to 2.2 mm with a single notch with a notch angle of 45° and a notch tip radius of 0.25 mm were used.

[0059] ~Environmental Stress Crack Resistance Test (ESCR)~ To evaluate the chemical resistance of the molded article, an environmental stress crack resistance test was carried out in accordance with JIS K7108 under the conditions of 50°C using a surfactant (manufactured by Nippon Oil & Fats, (product name) Nonion NS210 (10 wt% aqueous solution)) and 50°C. Test pieces were cut out from the blow molded article to prepare test pieces of 38 mm x 13 mm x 2.0 to 2.2 mm.

[0060] ~Skin of the molded body~ The appearance of the surface of the resulting blow molded article was evaluated visually. ◯: No melt fracture occurred and no gels or the like were observed. ×: Melt fracture or gelation occurred.

[0061] ~Drop Strength~ The resulting blow molded bodies were filled with water until they reached the top and sealed, and then dropped vertically from a height of 3 m with the bottom of the molded bodies facing down in a drop test. Three containers were then visually inspected and rated as ◯ if no cracks were found, and × if even one crack was found.

[0062] Preparation Example 1 (1) Preparation of organically modified clay 300 ml of industrial alcohol (manufactured by Japan Alcohol Sales Co., Ltd., (trade name) Ekinen F-3) and 300 ml of distilled water were placed in a 1-liter flask, 15.0 g of concentrated hydrochloric acid and 42.4 g (120 mmol) of dimethylbehenylamine (manufactured by Lion Specialty Chemicals, (trade name) Lipomin DM22D) were added, and the mixture was heated to 45°C to disperse 100 g of synthetic hectorite (manufactured by BYK Additives Limited, (trade name) Laponite RDS), and then the mixture was heated to 60°C and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600 ml of hot water at 60°C and dried in a dryer at 85°C for 12 hours to obtain 125 g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 10 μm.

[0063] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.628 g of diphenylmethylene(cyclopentadienyl)(2-diethylamino-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0064] Preparation Example 2 (1) Preparation of organically modified clay The same procedure as in Preparation Example 1 was followed.

[0065] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and a reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.669 g of diphenylmethylene(cyclopentadienyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride and 142 ml of a hexane solution of 20 wt% triisobutylaluminum, and the mixture was stirred at 60°C for 3 hours. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and then 200 ml of hexane was added to obtain a suspension of a catalyst for production (solid weight content: 12.5 wt%).

[0066] Preparation Example 3 (1) Preparation of organically modified clay In a 1-liter flask, 300 ml of industrial alcohol (product name Ekinen F-3, manufactured by Japan Alcohol Sales Co., Ltd.) and 300 ml of distilled water were added, and 15.0 g of concentrated hydrochloric acid and dioleylmethylamine ((C 18 H 35 )2(CH3)N, 63.7g (120mmol) of (Lipomin MO, manufactured by Lion Specialty Chemicals Co., Ltd.) was added and heated to 45℃, after which 100g of synthetic hectorite (Laponite RD, manufactured by BYK Co., Ltd.) was dispersed, and the temperature was raised to 60℃ and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600ml of water at 60℃ and dried in a dryer at 85℃ for 12 hours to obtain 130g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 15μm.

[0067] (2) Preparation of catalyst suspension for production After replacing the air in a 300 ml flask equipped with a thermometer and a reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by the addition of 0.392 g (1 mmol) of bis(indenyl)zirconium dichloride and 142 ml of a 20 wt% hexane solution of triisobutylaluminum, and stirring for 3 hours at 60°C. After cooling to room temperature, the supernatant was removed and washed twice with 220 ml of hexane, followed by the addition of 220 ml of hexane to obtain a suspension of a catalyst for production (solid weight content: 12.0 wt%).

[0068] Manufacturing Example 1 As described below, a bimodal polyethylene ethylene-based resin (III-1) was produced by two-stage polymerization in which the polymerization of component (III-1) was successively carried out after the polymerization of component (III-1). The ethylene-based resin (III-1) had an HLMFR of 2.3 g / 10 min and an [η] of 6.5 dl / g.

[0069] Manufacturing of component (A-1) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dL / g.

[0070] Manufacture of component (B-1) and ethylene resin (C-1) After polymerization of component (a-1), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 9 hours to polymerize component (b-1), thereby producing ethylene-based resin (c-1), which is an ethylene homopolymer. During the polymerization, 800g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-1) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0071] Manufacturing Example 2 As described below, a bimodal polyethylene ethylene resin (III-2) was produced by two-stage polymerization in which the polymerization of component (III-2) was successively carried out after the polymerization of component (III-2). The ethylene polymer (III-2) had an HLMFR of 3.1 g / 10 min and an [η] of 4.1 dl / g.

[0072] Manufacturing of component (A-2) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 2 were added, and the temperature was raised to 70°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-2) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 10 dl / g.

[0073] Manufacture of component (B-2) and ethylene resin (B-2) After polymerization of component (a-2), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.87MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 4 hours to polymerize component (b-2), thereby producing ethylene-based resin (c-2), which is an ethylene homopolymer. During the polymerization, 800g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-2) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0074] Production Example 3 As described below, a bimodal polyethylene ethylene-based resin (III-3) was produced by two-stage polymerization in which the polymerization of component (III-3) was successively carried out after the polymerization of component (III-3). The ethylene-based resin (III-3) had an HLMFR of 1.5 g / 10 min and an [η] of 7.2 dl / g.

[0075] Manufacturing of component (A-1) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 5 hours. During the polymerization, 500 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dL / g.

[0076] Manufacture of component (B-3) and ethylene resin (B-3) After polymerizing component (a-3), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 5 hours to polymerize component (b-3), thereby producing ethylene-based resin (c-3), which is an ethylene homopolymer. During the polymerization, 500g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-3) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0077] Production Example 4 As described below, a bimodal polyethylene ethylene resin (III-4) was produced by two-stage polymerization in which the polymerization of component (III-4) was successively carried out after the polymerization of component (III-4). The ethylene resin (III-4) had an HLMFR of 7.1 g / 10 min and an [η] of 6.0 dl / g.

[0078] Manufacturing of component (A-4) In a 10-liter autoclave, 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 1 were added, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of component (A-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dL / g.

[0079] Manufacture of component (B-4) and ethylene resin (B-4) After polymerization of component (a-4), ethylene was continuously fed so that the ethylene partial pressure was maintained at 0.50MPa at 60°C, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500ppm, and slurry polymerization was carried out for 8 hours to polymerize component (b-4), thereby producing ethylene-based resin (c-4), which is an ethylene homopolymer. During the polymerization, 800g of ethylene was consumed in terms of polyethylene, and the [η] of component (b-4) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0dl / g.

[0080] Production Example 5 An ethylene-based resin (III-5) which is a monomodal polyethylene was produced as follows. The ethylene-based resin (III-5) had low fluidity and the HLMFR could not be measured.

[0081] Manufacturing of component (Ha-5) 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the catalyst for production obtained in Preparation Example 1 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.80 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 200 g of ethylene was consumed in terms of polyethylene, and the [η] of the component (Ha-5) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 22 dL / g.

[0082] Production Example 6 An ethylene-based resin (Ha-6), which is a monomodal polyethylene, was produced as follows.

[0083] Manufacturing of component (Ha-6) 6 liters of hexane, 5.5 ml of hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the catalyst for production obtained in Preparation Example 1 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously supplied so that the ethylene partial pressure could be maintained at 0.50 MPa, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 4500 ppm, and slurry polymerization was carried out for 1 hour. During the polymerization, 100 g of ethylene was consumed in terms of polyethylene, and the [η] of the component (Ha-6) calculated from the relationship with the hydrogen concentration in the system during the polymerization reaction was 2.0 dL / g.

[0084] Production Example 7 A high density polyethylene (II-1) was produced as follows.

[0085] Production of component (II-1) 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (corresponding to 310 mg of solid content) of the suspension of the production catalyst obtained in Preparation Example 3 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.75 MPa, and slurry polymerization was carried out for 1 hour. During the polymerization, 100 g of ethylene was consumed in terms of polyethylene, and the MFR of the obtained (Ni-1) was 1.0 g / 10 min.

[0086] Production Example 8 A high density polyethylene (polyethylene (II)-2) was produced as follows.

[0087] Production of component (II-2) 6 liters of hexane, 5.5 ml of a hexane solution of 20 wt% triisobutylaluminum, and 2.50 g (equivalent to 310 mg of solid content) of the suspension of the catalyst for production obtained in Preparation Example 3 were added to a 10-liter autoclave, and the temperature was raised to 60°C. Ethylene was continuously fed so that the ethylene partial pressure could be maintained at 0.8 MPa, and hydrogen was intermittently added so that the hydrogen concentration in the gas phase of the autoclave was 2500 ppm, and slurry polymerization was carried out for 1 hour. 100 g of ethylene was consumed in terms of polyethylene during the polymerization, and the MFR of the obtained (D-2) was 20 g / 10 min.

[0088] Example 1 200 g of the ethylene-based resin (H-1) obtained in Production Example 1, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 957 kg / m 3 800 g of ethylenediaminetetraacetate (800 g) and 2 g of an antioxidant (manufactured by BASF, product name: Irganox B225) were dry-blended, and then melt-kneaded at 220°C, 30 rpm, and a discharge rate of 0.8 kg / h using a twin-screw extruder (manufactured by Toyo Seiki Seisakusho, product name: Labo Plastomill parallel twin-screw extruder 2D25S) to obtain a polyethylene composition (e-1). The MFR of the polyethylene composition (e-1) was 0.03 g / 10 min.

[0089] Furthermore, 120 g of the obtained polyethylene composition (E-1) was extruded in a blow molding machine (manufactured by Placo Corporation, (product name) DA-50S) at a cylinder temperature of 220°C and a screw rotation speed of 30 rpm to mold a container having a capacity of 10 L as a blow molded article. The evaluation results of each are shown in Table 1.

[0090] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 68 kJ / m 2 and 180h.

[0091] Example 2 A polyethylene composition (E-2) was obtained and a blow molded article was obtained in the same manner as in Example 1, except that 250 g of the ethylene resin (E-1) obtained in Production Example 1 and 750 g of the polyethylene (E-1) obtained in Production Example 7 were used. The MFR of the resulting polyethylene composition (E-2) was 0.3 g / 10 min.

[0092] The evaluation results are shown in Table 1.

[0093] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 68 kJ / m 2 and 45h.

[0094] Example 3 500 g of the ethylene-based resin (H-1) obtained in Production Example 1, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 4010 (MFR = 5.4 g / 10 min, density = 964 kg / m 3 A polyethylene composition (e-3) was obtained, and a blow molded article was obtained, in the same manner as in Example 1, except that 500 g of NH4010 (hereinafter sometimes referred to as NH4010) was used. The MFR of the polyethylene composition (e-3) was 2.3 g / 10 min.

[0095] The evaluation results are shown in Table 1.

[0096] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 50 kJ / m 2 and 40h.

[0097] Example 4 A polyethylene composition (E-4) was obtained, and a blow molded article was obtained, in the same manner as in Example 1, except that 250 g of the ethylene resin (E-2) obtained in Production Example 2 and 750 g of the polyethylene (E-1) obtained in Production Example 7 were used. The MFR of the polyethylene composition (E-4) was 0.3 g / 10 min.

[0098] The evaluation results are shown in Table 1.

[0099] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 60 kJ / m 2 and 48h.

[0100] Example 5 A polyethylene composition (E-5) was obtained, and a blow molded article was obtained, in the same manner as in Example 1, except for using 100 g of the ethylene resin (E-3) obtained in Production Example 3 and 900 g of the polyethylene (E-1) obtained in Production Example 7. The MFR of the polyethylene composition (E-5) was 0.05 g / 10 min.

[0101] The evaluation results are shown in Table 1.

[0102] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 70 kJ / m 2 and 170h.

[0103] Example 6 A polyethylene composition (E-6) was obtained, and a blow molded article was obtained, in the same manner as in Example 1, except that 900 g of the ethylene resin (E-4) obtained in Production Example 4 and 100 g of the polyethylene (E-1) obtained in Production Example 7 were used. The MFR of the polyethylene composition (E-6) was 0.03 g / 10 min.

[0104] The evaluation results are shown in Table 1.

[0105] The surface of the blow molded product was in good condition with no melt fracture. In addition, no cracks were observed in the drop test. The Charpy impact strength and ESCR measured using a test piece cut from the blow molded product were 72 kJ / m 2 and 160h.

[0106] [Table 1]

[0107] Comparative Example 1 100 g of the ethylene resin (H-5) obtained in Production Example 5, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 957 kg / m 3 A polyethylene composition (e-7) was obtained, and a blow-molded article was obtained, in the same manner as in Example 1, except that 900 g of the polyethylene composition (e-7) was used. The MFR of the polyethylene composition (e-7) was 0.02 g / 10 min.

[0108] The evaluation results are shown in Table 2.

[0109] Melt fracture occurred in the skin of the blow molded article, and gel was also observed on the surface.

[0110] Comparative Example 2 100 g of the ethylene-based resin (H-6) obtained in Production Example 6, polyethylene (manufactured by Tosoh Corporation, (product name) Nipolon Hard 8D01A (MFR = 0.05 g / 10 min, density = 957 kg / m 3 A polyethylene composition (e-8) was obtained, and a blow-molded article was obtained, in the same manner as in Example 1, except that 900 g of polyethylene terephthalate was used. The MFR of the polyethylene composition (e-8) was 0.3 g / 10 min.

[0111] The results of each evaluation are shown in Table 2. The surface of the blow molded article was good with no melt fracture, but both the Charpy impact strength and ESCR were low, indicating that the strength and durability were poor.

[0112] Comparative Example 3 250 g of the polyethylene resin (III-5) obtained in Production Example 5 and 750 g of the ethylene resin (III-6) obtained in Production Example 6 were dry blended. The Tm of the obtained blend was bimodal, being 136°C and 142°C. A polyethylene composition (III-9) was obtained in the same manner as in Example 1, except that 200 g of the above blend and 800 g of the polyethylene (III-9) obtained in Production Example 7 were used, and a blow molded article was obtained. The MFR of the polyethylene composition (III-9) was 0.6 g / 10 min.

[0113] The results of each evaluation are shown in Table 2. Gel was observed on the surface of the blow molded article.

[0114] Comparative Example 4 A polyethylene composition (E-10) was obtained and a blow molded article was obtained in the same manner as in Example 1, except that 200 g of the ethylene resin (E-1) obtained in Production Example 1 and 800 g of the polyethylene (E-1) obtained in Production Example 9 were used. The MFR of the polyethylene composition (E-10) was 0.05 g / 10 min.

[0115] The evaluation results are shown in Table 2. Gel was generated on the surface of the blow molded article, and the Charpy impact strength and ESCR were poor.

[0116] [Table 2] [Industrial Applicability]

[0117] The blow molded article of the present invention is expected to have excellent mechanical strength, thin wall thickness, long life, and environmental load resistance.

Claims

1. A blow molded article, characterized in that it is made of a polyethylene composition containing an ethylene-based resin (c) satisfying the following characteristics (c-a) and (c-b) and a polyethylene (d) satisfying the following characteristics (d-a) and (d-b). Characteristics (ha): Melt flow rate (HLMFR) of 0.01 to 100 g / 10 min at a temperature of 190°C and a load of 21.6 kg in accordance with JIS 6922-2:1997. Characteristics (hab): The elution curve measured by gel permeation chromatography is bimodal. Property (ii a): Melt flow rate (MFR) of 0.01 to 10 g / 10 min at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS 6922-2:1997. Property (ii b): Density measured according to JIS K6922-1 (1997) is 925 to 980 kg / m 3 .

2. 2. The blow molded article according to claim 1, wherein the ethylene-based resin (c) also satisfies the following characteristic (cc): Property (c): The crystal melting peak (Tm) in the first scan measured using a differential scanning calorimeter by heating from 0° C. to 230° C. at a heating rate of 10° C. / min (1st scan) is single-peaked.

3. 3. The blow molded article according to claim 1, wherein the ethylene-based resin (c) also satisfies the following characteristic (cd): Characteristics (had): the molecular weight distribution, calculated as standard polyethylene, measured by gel permeation chromatography is 4.0 or more and less than 50.

4. 3. The blow molded article according to claim 1, wherein the ethylene-based resin (c) also satisfies the following characteristic (c) : Characteristics (Ae): The titanium content in the ash is less than 2 ppm and the chlorine content in the ash is less than 50 ppm.

5. 3. The blow molded article according to claim 1, wherein the ethylene-based resin (c) satisfies the following characteristic (cf): (Ha f): The elution curve measured by gel permeation chromatography has two peaks, and when the elution curve is expressed as a differential molecular weight distribution (x-axis: Log [M], y-axis: differential distribution value) and the peak is divided into two normal distributions according to the following formula (i), the following (Ha f-1) to (Ha f-3) are satisfied. f(x)=a×(1 / (2π(σ 2 )) (1/2) ) x 2 ) / (2(s 2 ))) formula (i) (Here, a is the peak intensity, σ is the standard deviation, x is the variable, and μ is the average.) (Ha f-1): The weight average molecular weight calculated as linear polyethylene based on the peak on the high molecular weight side is 900,000 to 5,000,000. (Ha f-2): The weight average molecular weight calculated as linear polyethylene based on the peak on the low molecular weight side is 10,000 to 500,000. (Cf-3): The weight ratio of the high molecular weight peak / the weight ratio of the low molecular weight peak is greater than 5 / 95 and smaller than 80 / 20.

6. Charpy impact strength measured at 23°C is 20 kJ / m 2 3. The blow molded article according to claim 1 or 2, characterized in that:

7. 3. The blow molded article according to claim 1, wherein the ethylene-based resin (iii) is an ethylene homopolymer.

Citation Information

Patent Citations

  • JP1973068853A

  • Thermal transfer type sheet

    JP1989005888A

  • Modifier for polyethylene resin, manufacturing method of polyethylene resin composition using the same and manufacturing method of molded body

    JP2017179304A

  • Ultra high molecular weight polyethylene

    JP2021172716A

  • polyethylene resin composition

    JP4173444B2